Activities of mitochondrial respiratory chain complexes in platelets of patients with Alzheimer's disease and depressive disorder - Fišar, Zdeněk; Hansíková, Hana; Křížová, Jana; Jirák, Roman; Kitzlerová, Eva; Zvěřová, Martina; Hroudová, Jana; Wenchich, László; Zeman, Jiří; Raboch, Jiří (Mitochondrion, 2019)
We analyzed activities of complex I, II, III, and IV, and citrate synthase (CS) in patients with major depressive disorder (MDD) or Alzheimer's disease (AD) presenting with or without depression. Associations of these parameters with disease or disease severity were observed in both AD and MDD; however, mean values of mitochondrial parameters were significantly altered in AD but not in MDD. Potential mitochondrial dysfunction in MDD seems not to be caused by disturbed activity of CS or respiratory complexes. In AD, a decrease in the activity of CS and complex IV may cause mitochondrial dysfunction, whereas an increase in activities of other mitochondrial complexes or their ratios to CS may be an adaptive response. The data indicate that comorbid depression in AD is associated with increased complex II activity. The mitochondrial parameters measured can be included in the panel of biomarkers of AD.
Keywords: Mitochondria; Male; biologické markery; elektronový transportní řetězec; Coenzyme Q(10); Biomarkers; Depressive disorder; Blood Platelets; Depressive Disorder, Major; mitochondriální membrány; Adult; Alzheimerova nemoc; Alzheimer Disease; transport elektronů; dospělí; Aged; mužské pohlaví; senioři; Case-Control Studies; Electron Transport Chain Complex Proteins; Citrate synthase; Respiratory complex; Alzheimer's disease; Electron Transport; senioři nad 80 let; trombocyty; lidé; ženské pohlaví; studie případů a kontrol; Humans; depresivní porucha unipolární; Aged, 80 and over; Female; Mitochondrial Membranes; lidé středního věku; mitochondrie; Middle Aged